Avifauna asociada a sistemas agroforestales de cacao (Theobroma cacao) en las comunidades indígenas Shampuyacu y Alto Mayo, San Martín – Perú - Tuesta Cometivos, Gino Anthony (2023)
From August to November 2022, the avifauna associated with cocoa agroforestry systems in Shampuyacu and Alto Mayo native communities, located in the department of San Martín, were evaluated. The objective was to evaluate the diversity, trophic guilds and conservation status of the avifauna associated with cocoa agroforestry systems in both communities. Using the point count census method, 93 bird species were recorded, distributed in 10 orders and 24 families, with Thraupidae and Tyrannidae being the families with the largest number of species, among the most dominant in Shampuyacu were Thraupis episcopus, Euphonia chlorotica and Todirostrum cinereum and in Alto Mayo, Thraupis episcopus, Tangara mexicana and Ramphocelus melanogaster, the latter endemic to Peru. The registered avifauna was 76.7 % similar for both native communities. Of the 13 trophic guilds, the omnivore included more bird species in both zones. According to the conservation categories, 13 species were found in Appendix II of CITES, in addition to Chaetocercus bombus, according to the IUCN, and D.S. 04 -2014 MINAGRI is “almost threatened”.